Time area histogram models for Himalayan watersheds - VERMA, M. P.; SINGH, MANISH; S. PATEL, R. A. (Journal of Soil and Water Conservation, 2020)
The present study based on the concept of watershed routing. This concept is based on the time area histogram (TAH) routing. The regeneration and prediction of the models were evaluated on the comparison of observed and computed direct runoff hydrographs in Chaukhutia and Gagas watersheds. The statistical measures such as integral square error, absolute relative errors in computed and observed peaks adopted for the performances evaluation of the watersheds. According to the statistical analysis, the model efficiency through the reservoir routing is quite high. However, in case of channel routing the model efficiency is also satisfactory. The other statistical parameter departure percentages of the watersheds are minimum. It means the observed and computed out puts are likely to be similar which indicates the model goodness of fit. According to these valuable findings it is evident that the most suitable weighting factors of the Chaukhutia and Gagas watersheds are 0.30 and 0.35, respectively. These weighting factors are useful for the computation of the peaks for the purpose of structural design and flood forecasting.